Virtual jury court: seeking harmonization between the emergency solutions caused by the pandemic of the new coronavirus and the observance of constitutional precepts - Ronald Pinheiro Rodrigues; Nigel Stewart Neves Patriota Malta (Revista Brasileira de Direito Processual Penal)
The Brazilian Judiciary has sought to promote the appropriate adaptations to the changes caused by the new coronavirus (Sars-CoV-2), with the holding of hearings and several other procedural acts, using videoconferencing instruments. This article addresses the proposal of the National Council of Justice (CNJ) for virtualization, during that period, of the sessions of the jury court, in the light of the constitutional precepts on the matter. The problematization focuses on the search for harmonization between the emergency solutions that arose in the pandemic context with the guidelines included in Recommendation nº 62/2020 of the referred internal control body of the Judiciary. Various issues are discussed, with emphasis on the constitutional debate, on criteria related to the jury's court, such as the argumentative prejudice, the prominence of the special procedure and the applicability of the legal provisions of videoconferencing to the rite under analysis, in addition to those related to secrecy of the votes and the incommunicability of the jurors, with notes for not incarceration measures. Based on a methodology based on a review of specialized literature, with a qualitative approach, a critical judgment is formulated about the constitutionality of the intention to virtualize the jury's special procedure, a proposal that took place especially under the adequate pretext of effect of the constitutional principle of reasonable duration of the process.